Interface Engineering of BCP Buffer Layers in Planar Heterojunction Perovskite Solar Cells With NiOx Hole Transporting Layers - He, Chunfeng; Zhang, Fayin; Zhao, Xin; Lin, Changjian; Ye, Meidan (Frontiers in Physics, 2018)
Bathocuproine (BCP) was first employed as the interface buffer layers between the PCBM and Ag layers to improve the performance of Cs0.08(MA0.17FA0.83)0.92Pb(I0.83Br0.17)3 perovskite solar cells based on NiOx hole transporting layers. The effect of different evaporation times on the performance of solar cells at the same evaporation temperature (100℃) was carefully investigated. The optimum device efficiency of 14.47% was obtained by evaporating BCP for 36 s, suggesting an enhancement of 14% as compared to the cell without BCP modification.